Copper ferrite synthesis from spent Li-ion batteries for multifunctional application as catalyst in photo Fenton process and as electrochemical pseudocapacitor. (May 2019) - Rocha, A.K.S.; Magnago, L.B.; Santos, J.J.; Leal, V.M.; Marins, A.A.L.; Pegoretti, V.C.B.; Ferreira, S.A.D.; Lelis, M.F.F.; Freitas, M.B.J.G.
Graphical abstract: Photocatalystic and electrochemical multifunctional properties of CuFe2 O4 synthesized using LIBs as raw materials. Highlights: CuFe2 O4 was synthesized with copper from spent lithium ion batteries (LIBs). Multifunctional properties of CuFe2 O4 -LIBs were analyzed. CuFe2 O4 -LIBs was applied as a catalyst in heterogeneous photo Fenton reaction. CuFe2 O4 -LIBs pseudocapacitive properties were studied by cyclic voltammetry. Abstract: In this study, from copper recycled from spent lithium-ion batteries (LiBs) is made the synthesis of cupper ferrite (CuFe2 O4 -LiB). X-ray diffraction, energy dispersive X-ray spectroscopy and inductively coupled plasma optical emission spectrometry (ICP OES) identified the structure and composition of CuFe2 O4 -LiB. Scanning electron microscopy and transmission electron microscopy showed agglomerates of nanometric spherical particles. This study investigated the multifunctionality of CuFe2 O4 -LiB. Photocatalytic properties were analyzed by monitoring the decolorization of methylene blue (MB) in a heterogeneous photo-Fenton process in the presence of solar radiation. Decolorization efficiency was 96.1% in 45 min of reaction. Ion chromatography detected formic and acetic acids as products of MB degradation, and by ICP OES measured lower concentrations of 0.09 mgL −1 and 0.37 mgL −1, respectively for iron and copper ions in the treated solution. CuFe2 O4 -LiB electrodes showed great reversibility, charge efficiency, and a specific capacitance of 2.4 Fg −1 (10.0 mVs −1 ), which are favorable characteristics for pseudocapacitors.